Pengaruh Faktor Demografi terhadap Tingkat Literasi Keuangan: Studi Pelaku UMKM Kab. Sarolangun - Muhammad Padilah; Putri Apria Ningsih; Nurrahma Sari Putri (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This research aims to determine and analyze the influence of demographic factors consisting of a person's income level, education level and age on the financial literacy level of MSME actors in Sarolangun district. The method used in this research is a quantitative method, and the data analysis method used is the coefficient of determination test. The sample in this study was ninety-five respondents by distributing a Likert scale questionnaire. The research results show that 51.6% of respondents fall into the high level of financial literacy category, and 48.4% of respondents fall into the moderate financial literacy category. There is a positive and significant influence between income level (X1) on financial literacy (Y). This is proven by the t value of 2,543 t table > 1.986 and the Sig value of 0.013 < 0.05, which means that H1 is accepted and H0 is rejected. Education level (X2) shows that it has a positive and significant influence on financial literacy (Y). This is proven by the calculated t value of 8.932 t table > 1.986 and the Sig value of 0.001 < 0.05, which means that H1 is accepted and H0 is rejected. Age (X3) shows that it has a positive and significant influence on financial literacy (Y). Proven by the calculated t value of 2.216 t table > 1.986 and the Sig value of 0.029 < 0.05 which means that H1 is accepted and H0 is rejected. Income level, education and age simultaneously influence financial literacy. It is known that the significance value of X1, so it can be concluded that H1 is accepted and H0 is rejected. The influence of these three variables is 62% and the remaining 28% is influenced by other variables outside this research.